Synergistic flame retardant effects between sepiolite and magnesium hydroxide in ethylene-vinyl acetate (EVA) matrix (eXPRESS Polymer Letters)
Some customers are reluctant to change, because the halogen-free solutions may have higher cost. This is one of the reasons that the synergistic effect is always the subject for researchers to pursue. The synergy between sepiolite and magnesium hydroxide (MH) in halogen-free flame retardant ethylene-vinyl acetate (EVA) copolymer was investigated in the paper through some common facilities, such as limiting oxygen index (LOI), UL-94 test, thermogravimetric analysis (TGA), differential thermal analysis (DTA) and cone calorimeter test (CCT). In the wake of the positive results from the LOI and UL-94 tests, the CCT data indicated not only the reduction of heat release rate (HRR) and mass loss rates (MLR), but also prolonged ignition time (TTI) and depressed smoke release (SR) were observed during combustion. Simultaneously, the tensile strength and Young’s modulus of the system were also much better improved with the increase of sepiolite added due to the hydrogen bonds between silanol groups attached to the sepiolite molecules and the ester groups of EVA. The synergistic mechanism has been discussed in the paper in terms of the barrier mechanism in the condensed phase.